2016
DOI: 10.1149/2.0221605jss
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Ni-Doped Colloidal Silica Abrasives and Their Chemical Mechanical Polishing Performances on Sapphire

Abstract: Chemical mechanical polishing (CMP) has become a widely accepted global planarization technology. Abrasive is one of the key elements in CMP process. In order to enhance material removal rate (MRR) and improve surface quality of sapphire substrate, a series of novel Ni-doped colloidal silica abrasives were prepared by seed-induced growth method. The CMP performances of composite abrasives on sapphire substrate were investigated using UNIPOL-1502 polishing equipment. The analyses on the surface of polished sapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Table 4 demonstrates the influence of the composite abrasives on the polishing efficiency of sapphire [89][90][91][92][98][99][100]105]. Typically, in the work of Lei's research group, they doped metal ions such as Co/Fe/Cu/Ni/Zn in SiO 2 to form metal-doped SiO 2 composite abrasives, and found that solid chemical reactions occurred on the surface of sapphire during the grinding process of composite abrasives and sapphire [94][95][96][97][98]. The intermediate layer such as CoAl 2 O/AlFeO 3 /Al 2 CuO 4 /NiAl 2 O 4 / Al 2 ZnO 4 was formed and was easy to be removed.…”
Section: Constructing Composite Abrasivesmentioning
confidence: 99%
“…Table 4 demonstrates the influence of the composite abrasives on the polishing efficiency of sapphire [89][90][91][92][98][99][100]105]. Typically, in the work of Lei's research group, they doped metal ions such as Co/Fe/Cu/Ni/Zn in SiO 2 to form metal-doped SiO 2 composite abrasives, and found that solid chemical reactions occurred on the surface of sapphire during the grinding process of composite abrasives and sapphire [94][95][96][97][98]. The intermediate layer such as CoAl 2 O/AlFeO 3 /Al 2 CuO 4 /NiAl 2 O 4 / Al 2 ZnO 4 was formed and was easy to be removed.…”
Section: Constructing Composite Abrasivesmentioning
confidence: 99%
“…14 Lei et al mixed some metal ions into the silica sol for C-plane sapphire CMP, such as La, Zn, Fe, Cu, and Ni ions, and found that AlLaO 3 , Al 2 ZnO 4 , AlFeO 3 , Al 2 CuO 4 , and NiAl 2 O 4 were easily formed and removed, which promoted the chemical reaction and improved the MRR. [15][16][17][18][19] Dai et al found that coating SiO 2 on the SiC surface significantly improved the polishing performance of the abrasive and increased the MRR of C-plane sapphire. 20 Lu et al found that the MRRs were improved and good surface morphology was obtained for C-, A-and R-plane sapphire by adding potassium persulfate (K 2 S 2 O 8 ) into the slurry.…”
mentioning
confidence: 99%
“…), and found AlLaO 3 /CoAl 2 O/AlFeO 3 / NiAl 2 O 4 /Al 2 CuO 4 /Al 2 ZnO 4 which are softer and easier to remove were formed. [18][19][20][21][22][23] Yin et al confirmed that solid-solid reaction occurred and aluminum silicate was formed, which has lower hardness and can be removed easily than sapphire itself during the CMP process. 24 Through preliminary investigations, it is found that ZnO can react with Al 2 O 3 under certain conditions to form ZnAl 2 O 4 .…”
mentioning
confidence: 99%